Case Series of 3 Patients Diagnosed With Atypical Hemolytic Uremic Syndrome Successfully Treated With Steroids, Plasmapheresis, and Rituximab. Issue 1 (29th December 2017) - Patterson, Jeffery M.; Bolster, Lauren; Larratt, Loree
Rationale: Atypical hemolytic uremic syndrome, which has a high probability of chronic kidney disease, morbidity, and mortality, needs to be promptly recognized when patients present with microangiopathic hemolysis. Presenting Concerns of the Patient: Three patients present with laboratory parameters consistent with a thrombotic microangiopathy. With a suspected diagnosis of thrombotic thrombocytopenic purpura, steroids with plasmapheresis were initiated. Diagnoses: With ADAMTS13 levels reported normal, the suspected diagnoses were reevaluated. Given ongoing renal impairment, atypical hemolytic uremic syndrome was strongly considered. Interventions: When local funding issues precluded the prompt use of eculizumab, 4 doses of weekly rituximab were trialed. Outcome: Over 2 years later, all 3 patients have sustained durable remissions defined by the absence of kidney impairment or laboratory investigations concerning for microangiopathic hemolytic relapse. Lessons Learned: In cases of a suspected autoimmune mechanism leading to atypical hemolytic uremic syndrome, long-term use of eculizumab may not be required.